ETIKA BERKOMUNIKASI DI MEDIA SOSIAL DALAM PERSPEKTIF AL-QUR’AN - Jumriani Jumriani; Hamdani Thaha; Amalia Harani (MADDIKA : Journal of Islamic Family Law, 2022)
This study discusses the Ethics of Communication on Social Media in the Perspective of the Qur'an. The purpose of this study is to describe the nature of communication ethics and to describe the view of the Qur'an regarding the ethics of communication in social media. The main problem that will be discussed in this study is how the essence of communication ethics and how the Qur'an views the ethics of communication on social media. This study used a qualitative research method with a thematic approach (Maudhu'i). The results of this study are (1). Islamic communication contains a message content, namely how to convey and apply Islamic values based on the Qur'an and Hadith in various aspects of human life or in other words that Islamic communication is related to a special message, namely da'wah, because the Qur'an and Hadith is a guideline for Muslims in life and life both in this world and in the hereafter.(2). From the six ethics of communication on social media from the perspective of the Qur'an, it can be understood that a communication is said to be good and does not conflict with Islamic religious teachings if it has implemented the communication ethics of 6Q, namely Qaulan ma'rufan (good and appropriate expressions), Qaulan kariman ( noble and precious words), Qaulan Maysuran (light and easy words), Qaulan balighan (words that make an impression on the soul and are easy to understand), Qaulan layyinan (gentle words), and Qaulan sadidan (true, straight and Honest ).